Modelling food security for staple protein in Indonesia using system dynamics approach. Issue 1 (1st January 2021) - Vanany, Iwan; Hajar, Granita; Utami, Ni Made Cyntia; Jaelani, Lalu Muhamad
Abstract: Poultry products such as chicken and eggs are part of staple foods and a source of protein in Indonesia so their availability for consumers needs to be ensured. Besides that, there is also a pressing need to reduce imports and keep prices stable. In Indonesia, poultry products are consumed more than beef, fish, and other staple protein products. This paper aims to develop a model of poultry product-supply chain using System Dynamics (SD) approach to a) capture the causality between variables in the availability of corn supply, feed mills, chicken production and customer demand; and b) to create a scenario where commodity demands can be fulfilled adequately so that food security can be strengthened. As the main ingredient of poultry feed, corn produce can be increased by using a tight planting method and the use of superior seeds. The sustainable availability of chicken feed is then expected to help boost poultry produce, in addition to improving the chicken farming methods per se. The proposed model is expected to provide a better understanding of poultry product food chain, which will subsequently inform relevant policymakers in formulating strategic programmes to strengthen food security.